Why is Your Cup of Coffee so Expensive? Because of a Tiny Bark Beetle! - Jiri Hulcr (EDIS)
Sometimes an insect pest attacking crops in places as far away as Indonesia or Ethiopia can be very important to us here in Florida. One such insect is the coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae: Scolytinae), a tiny (1.5 mm) bark beetle that originated in the highlands of central Africa. It would probably remain one of the many inconspicuous little beetles in the tropics, if not for the choice of its host: seeds of several Coffea species. This 3-page fact sheet was written by Jiri Hulcr, and published by the UF Department of School of Forest Resources and Conservation, October 2013. http://edis.ifas.ufl.edu/fr382